Variation between some apricot varieties in regard to flowering phenology in Boldogkôváralja, Hungary - Ezzat, A.; Amriskó, L.; G., G.; Mikita, T.; Nyéki, J.; Soltész, M.; Szabó, Z. (International Journal of Horticultural Science, 2012)
The aim of this study was the estimation of blossoming of 14 apricot cultivars in Boldogkôváralja in 2009, 2010 and 2011 seasons. And this will help growers to select appropriate varieties to their weather conditions. For this target the blooming period of 19 apricot varieties of different origin was observed in three subsequent years. There was no large difference in the beginning of blooming in the different years, and the greatest variation between the start date of flowering was about 1 to 3 days as the place of experiment site near to northern border and also, length of flowering period of apricot trees is also inversely related to date when blooming started. The little differences in flowering dates and flowering periods due to the high temperature through the three seasons of study.